DNA binding, antitubercular, antibacterial and anticancer studies of newly designed piano-stool ruthenium(ii) complexes - Navale, Govinda; Singh, Sain; Agrawal, Sonia; Ghosh, Chandrachur; Choudhury, Angshuman Roy; Roy, Partha; Sarkar, Dhiman; Ghosh, Kaushik (Dalton Transactions, 2022)
The chemotherapeutic potential of ruthenium(ii) complexes has recently attracted researchers' interest as antibacterial and anticancer agents. In this study, two novel half-sandwich imine-based Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6] (Ru-1) and [Ru(p-cymene)Cl(L-2)][PF6] (Ru-2)) were reported for their deoxyribonucleic acid (DNA) binding and antitubercular, antibacterial, and anticancer activities. The molecular structure of Ru-2 was obtained by single-crystal X-ray crystallography. DNA interaction studies were conducted by UV-Vis absorbance and fluorescence spectral titration which gave rise to DNA binding constants (K-b) of 1.32 x 10(6) and 1.82 x 10(6) for Ru-1 and Ru-2, respectively and the Stern-Volmer binding constant (K-SV) values for Ru-1 and Ru-2 were 1.7763 x 10(4) M-1 and 7.6 x 10(3) M-1, respectively. The in vitro antitubercular activity was evaluated against Mycobacterium tuberculosis H37Ra. The antibacterial potential of both the Ru-complexes was examined against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. The half-maximal inhibitory concentration (IC50) values for the antitubercular activity of Ru-1 and Ru-2 were 4.87 +/- 1.32 mu M and 5.78 +/- 0.54 mu M, respectively. A cytotoxic study of these complexes was performed against the human breast cancer cell line (MCF-7) and the human embryonic kidney cell line (HEK293) (normal cells). The study revealed meaningful activity of the Ru-1 complex against (cancer) MCF-7 cells, while the viability of HEK293 (normal) cells in the presence of Ru-2 was higher as compared to a reference drug 5FU. We suggest that these kinds of Ru-complexes could have potential for application in metallopharmaceuticals.

Design and synthesis of piano-stool ruthenium(II) complexes and their studies on the inhibition of amyloid ? (1-42) peptide aggregation - Singh, Sain; Navale, Govinda R.; Agrawal, Sonia; Singh, Haobam Kisan; Singla, Labhini; Sarkar, Dhiman; Sarma, Manabendra; Choudhury, Anghuman Roy; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Misfolding , protein aggregation have been linked to numerous human neurodegenerative disorders such as Alzheimer's, prion , Parkinson's diseases. Ruthenium (Ru) complexes have received considerable attention in studying protein aggregation due to their interesting photophysical and photo properties. In this study, we have synthesized the novel Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6](Ru-1), and [Ru(p-cymene)Cl(L-2)][PF6](Ru-2)) and investigated their inhibitory activity against the bovine serum albumin (BSA) aggregation and the A beta 1-42 peptides amyloid formation. Several spectroscopic methods were used to characterize these complexes, and the molecular structure of the complex was determined by X-ray crystallography. Amyloid aggregation and inhi-bition activities were examined using the Thioflavin-T (ThT) assay, and the secondary structures of the protein were analyzed by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). The cell viability assay was carried out on the neuroblastoma cell line, revealing that the complex Ru-2 showed better protective effects against A beta 1-42 peptide toxicity on neuro-2a cells than the complex Ru-1. Molecular docking studies elucidate the binding sites and interactions between the Ru-complexes and A beta 1-42 peptides. The exper-imental studies revealed that these complexes significantly inhibited the BSA aggregation and A beta 1-42 amyloid fibril formation at 1:3 and 1:1 molar concentrations, respectively. Antioxidant assays demonstrated that these complexes act as antioxidants, protecting from amyloid-induced oxidative stress. Molecular docking studies with the monomeric A beta 1-42 (PDB: 1IYT) show hydrophobic interaction, and both complexes bind preferably in the central region of the peptide and coordinate with two binding sites of the peptide. Hence, we suggest that the Ru-based complexes could be applied as a potential agent in metallopharmaceutical research against Alzheimer's disease.
Keywords: Aggregation; Amyloid ?(1-42) peptide; DFT computation; Fibrillization; Molecular docking; Ruthenium complexes

Inhibition of amyloid β1-42 peptide aggregation by newly designed cyclometallated palladium complexes - Saini, Rahul; Navale, Govinda R.; Singh, Sain; Singh, Haobam Kisan; Chauhan, Rahul; Agrawal, Sonia; Sarkar, Dhiman; Sarma, Manabendra; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Uncontrolled amyloid aggregation is a frequent cause of neurodegenerative disorders such as prions and Alzheimer's disease (AD). As a result, many drug development approaches focus on evaluating novel molecules that can alter self-recognition pathways. Herein, we designed and synthesized the cyclometallated pyrene (Pd-1 and Pd-3) and anthracene (Pd-2) based palladium complexes ([Pd((L-1)Cl] Pd-1, [Pd(L-2)Cl](Pd-2), and [Pd(L-3)Cl] (Pd-3)). This study explores the effect of these complexes on the aggregation, fibrillation, and amyloid formation of bovine serum albumin (BSA) and A beta(1-42) peptide. Several spectroscopic methods were used to characterize all the Pd-complexes, and the molecular structure of Pd -3 was determined by X-ray crystallography. The secondary structures were studied using circular dichroism (CD) and transmission electron microscopy (TEM), while am-yloid aggregation and inhibitory activities were investigated using the Thioflavin-T (ThT) fluorescence assay. Molecular docking of the Pd-complex (Pd-3) was done using fibril (PDB: 2BEG) and monomeric (PDB: 1IYT) peptides using Auto-dock Vina. As a result, the hydrogen bonding and hydrophobic interaction between the aromatic rings of the Pd-complexes and the amino acids of amyloid-beta peptides significantly reduced the pro-duction of ordered beta-sheets of amyloid fibrils and protein aggregation in the presence of Pd-2 and Pd-3 complexes.
Keywords: A beta(1-42) peptide; Aggregation and molecular docking; Palladium complex